Semi-synthesis of chondroitin sulfate-E from chondroitin sulfate-A - Cai, Chao (2012)
Chondroitin sulfate-E (chondroitin-4, 6-disulfate) was prepared from chondroitin sulfate-A (chondroitin-4 - sulfate) by regioselective sulfonation, performed using trimethylamine sulfur trioxide in formamide under argon. The structure of semi-synthetic chondroitin sulfate-E was analyzed by PAGE, (1)H NMR, (13)C NMR, 2D NMR and disaccharide analysis and compared with natural chondroitin sulfate-E. Both semi-synthetic and natural chondroitin sulfate-E were each biotinylated and immobilized on BIAcore SA biochips and their interactions with fibroblast growth factors displayed very similar binding kinetics and binding affinities. The current semi-synthesis offers an economical approach for the preparation of the rare chondroitin sulfate-E from the readily available chondroitin sulfate-A.